Conclusion: Sexual Abuse, Science and Church - Lütz, Manfred (Sexual abuse in the Catholic Church, 2004)
Proceedings of the conference "Abuse of children and young peole by catholic priests and religious" (Vatican City, April 2-5, 2003)